Implementasi Komunikasi Master – Slave pada PLC OMRON CP1H - Galuh Purnama Aji; Bakhtiar Alldino Sumbodo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2021)
Almost all factories now use automated system, where the factory using a control system that can do the work itself and the operator are not too play an active role. With a system that runs automatically is expected to yield a production will increase with the quality of the product that generated the same no difference. Common control system used by the company in the form of PLC (Programmable Logic Controller). The system uses two OMRON CP1H PLC as drivers and integrated with CX-Designer HMI that communicate through one to one NT link and PLC controlled by CX-Programmer through the communication port USB Peripheral and RS-232. Both the input output PLC connected with USB-OPTO-RLY88 which is integrated with visual studio 2017 software using Host Link communication. The result of testing a system that compares the response time between communication port USB Peripheral with RS-232 and parallel ladder diagram with sequential ladder diagram, obtained 400 data of response time when the system was working. The result of data comparison tells that USB Peripheral port has a performance about 15% more efficient compared to the RS-232 port.